The cruel and unusual phenomenology of solitary confinement - Gallagher, Shaun (Frontiers in Psychology, 2014)
What happens when subjects are deprived of intersubjective contact? This paper looks closely at the phenomenology and psychology of one example of that deprivation: solitary confinement. It also puts the phenomenology and psychology of solitary confinement to use in the legal context. Not only is there no consensus on whether solitary confinement is a “cruel and unusual punishment,” there is no consensus on the definition of the term ‘cruel’ in the use of that legal phrase. I argue that we can find a moral consensus on the meaning of ‘cruelty’ by looking specifically at the phenomenology and psychology of solitary confinement.